Review of the Fund's Strategy on Overdue Financial Obligations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper reviews progress under the Fund's strengthened cooperative strategy on overdue financial obligations. The level and structure of arrears to the Fund remained broadly unchanged since the last review. Total arrears to the Fund amounted to SDR 1,303.9 million at end-June 2011, a decline of about SDR 5.5 million since the last review. While payments to the Fund by Sudan and Zimbabwe were in excess of new obligations falling due since the last review, Somalia's arrears increased further.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: PP; The Fund; Sudan